2017
DOI: 10.1007/s41465-017-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Measures of Transfer Effects Missing the Target?

Abstract: Repeated and targeted training of working memory typically leads to improvements as observed using cognitive assessments of working memory and different methods of brain imaging. A more controversial topic is whether these improvements transfer to improvements in other cognitive functions and if behavior in everyday life is impacted. If such transfer is the overarching goal with cognitive training, then determining the relevant markers of this should be deemed essential. However, research publications within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…In particular, the second study by Aries [77] indicated that WM was somewhat decoupled from contextual performance such as comprehension, contrary to accepted theory that WM underpins complex thought [65]. While strong WM capacity as a contingent factor for performance across education and work has been well documented (see introductory sections), any assumption that improvements in WM will therefore mediate improvements in higher-order, functional skills was not demonstrated by our synthesis or in the extant literature; an observation echoed by some contemporary WM authors [85], [176], [177].…”
Section: Discussion: Implications For Research and Practicecontrasting
confidence: 59%
“…In particular, the second study by Aries [77] indicated that WM was somewhat decoupled from contextual performance such as comprehension, contrary to accepted theory that WM underpins complex thought [65]. While strong WM capacity as a contingent factor for performance across education and work has been well documented (see introductory sections), any assumption that improvements in WM will therefore mediate improvements in higher-order, functional skills was not demonstrated by our synthesis or in the extant literature; an observation echoed by some contemporary WM authors [85], [176], [177].…”
Section: Discussion: Implications For Research and Practicecontrasting
confidence: 59%
“…The recent debate about strategies for enhancing human cognitive abilities has concerned mostly pharmacological, environmental, or genetic factors (Dubljević, Knafo & Venero, 2015) and cognitive training interventions in healthy populations (Klingberg, 2010;Colzato, 2017). Outcomes are typically measures of training-induced transfer (e.g., Söderqvist & Nutley, 2017), based on the notion that systematically engaging a specific cognitive skill will enhance performance in untrained tasks supported by that skill. This line of research has received increasing attention; however, low comparability, statistical shortcomings and low ecological validity have limited its impact on the field (Moreau, Kirk, & Waldie, 2016;Söderqvist & Nutley, 2017;Cremen & Carson, 2017).…”
Section: Embodied Perspectives On Behavioral Cognitive Enhancementmentioning
confidence: 99%
“…Outcomes are typically measures of training-induced transfer (e.g., Söderqvist & Nutley, 2017), based on the notion that systematically engaging a specific cognitive skill will enhance performance in untrained tasks supported by that skill. This line of research has received increasing attention; however, low comparability, statistical shortcomings and low ecological validity have limited its impact on the field (Moreau, Kirk, & Waldie, 2016;Söderqvist & Nutley, 2017;Cremen & Carson, 2017).…”
Section: Embodied Perspectives On Behavioral Cognitive Enhancementmentioning
confidence: 99%
“…Nonetheless, given the common assumption that cognitive training approaches are broadly beneficial, it would be valuable if researchers would routinely include measures that serve at least as proxies for everyday life. This issue is specifically addressed in the opinion paper by Söderqvist and Bergman Nutley (2017), which focuses on the issue of transfer using working-memory training as an example. They point out that the current literature often lacks a theoretically driven approach to select and justify the outcome measures to assess transfer.…”
mentioning
confidence: 99%
“…Again, this illustrates the need for more research addressing these issues (cf. Söderqvist and & Bergman Nutley, 2017). …”
mentioning
confidence: 99%